Analisis Variasi Suhu Terhadap Kekuatan Tarik Bio Filament Berbahan PLA dan Serat Pati Kulit Singkong - Afta Nobby Waskita (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The problem of conventional plastic waste that is not easily degradable has prompted research into environmentally friendly alternative materials. This study aims to analyze the effect of extrusion temperature variations on the tensile strength of biofilaments made from Polylactic Acid (PLA) and cassava peel starch fibers through the filament extrusion process. Biofilaments were produced with three processing temperature variations, namely 150°C, 160°C, and 170°C with standard ASTM D2256 testing dimensions. Mechanical testing was carried out using a Universal Testing Machine to determine the tensile strength and strain values of each temperature variation. The results showed that an increase in extrusion temperature had a significant effect on the decrease in the mechanical strength of the material. A temperature of 150°C produced the highest tensile strength value of 97.78 MPa and an elongation of 0.28%, while a temperature of 170°C reduced the tensile strength to 38.5 MPa and an elongation of 0.19%. The decline in mechanical quality at high temperatures indicates thermal degradation of the PLA polymer chains and weakening of the matrix-filler integration. Thus, an extrusion temperature of 150°C is considered optimal for producing cassava peel PLA biofilament with the best tensile strength.